Pengaruh Profitabilitas, Ukuran Perusahaan, dan Leverage Terhadap Audit Report Lag : (Studi Empiris pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2020 - 2023) - Agnes Br Tarigan; Veronica Setiawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this research was to examine the relationship between audit report latency and profitability, firm size, and leverage. This study falls under the category of quantitative research. The data utilised in it comes from secondary sources, specifically the company's annual financial report that can be found on the Indonesia Stock Exchange (IDX) website for the years 2020–2023. With the use of a purposive sampling strategy, we were able to collect 236 pieces of observational data from 59 different companies. The statistical package used for data processing in this study is SPSS 27, and the kind of data analysis that was employed is multiple linear regression analysis. The study found that audit report lag is positively but insignificantly affected by leverage, firm size negatively but significantly affects audit report lag, and profitability negatively but insignificantly affects audit report lag.